Survival from Primary Abdominal Lymphoma Presenting with a Mass and Obstructive Jaundice - Hugh J Freeman; Andrew M Seal (Canadian Journal of Gastroenterology)
A 68-year-old female presented with an enlarged and nontender palpable gallbladder and clinical features of obstructive jaundice. Subsequent laboratory investigations confirmed the presence of cholestasis associated with an obstructing mass in the region of the common hepatic duct. Pathological evaluation of the mass revealed a localized abdominal lymphoma. Treatment with chemotherapy and radiation resulted in complete clinical remission (for almost 14 years at the last evaluation). Primary abdominal lymphoma may involve the hilar region and present as a localized mass. Precise tissue diagnosis is essential to permit an aggressive management approach with the potential for significant clinical benefit.